2020
DOI: 10.3390/ijerph17238831
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental Factors on the Prevalence Changes of Allergic Diseases in Elementary School Students in Ulsan, Korea: A Longitudinal Study

Abstract: We examined the effect of long-term changes in environmental factors on the prevalence of allergic diseases in elementary school students in Ulsan, Korea. This longitudinal study was conducted among 390 students who were enrolled from three elementary schools in Ulsan in both the first (2009–2010) and second survey (2013–2014). The International Study of Asthma and Allergies in Childhood questionnaire was used to determine the prevalence of allergic diseases and hazardous environmental factors. Generalized est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
3
6
0
2
Order By: Relevance
“…[23][24][25] Severe air pollution is associated with increased prevalence and severity of AR through numerous allergy-related pollutants including PM2.5 particles. 3,6,7 In our study, we observed increased expression of OVA-sIgE in AR rats, especially after PM2.5 exposure, which showed a positive correlation with the occurrence of allergic nasal symptoms.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…[23][24][25] Severe air pollution is associated with increased prevalence and severity of AR through numerous allergy-related pollutants including PM2.5 particles. 3,6,7 In our study, we observed increased expression of OVA-sIgE in AR rats, especially after PM2.5 exposure, which showed a positive correlation with the occurrence of allergic nasal symptoms.…”
Section: Discussionsupporting
confidence: 63%
“…Rosmarinic acid is considered as a promising alternative treatment for allergic diseases including AR, owing to its anti‐inflammatory, anti‐allergic, antibacterial, and antitumor properties 23–25 . Severe air pollution is associated with increased prevalence and severity of AR through numerous allergy‐related pollutants including PM2.5 particles 3,6,7 . In our study, we observed increased expression of OVA‐sIgE in AR rats, especially after PM2.5 exposure, which showed a positive correlation with the occurrence of allergic nasal symptoms.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Two review articles concluded that household airborne chemical exposure can be associated with atopic dermatitis. 14,24 Redecoration and buying new furniture can be associated with a higher prevalence of atopic dermatitis in pre-school children 15,17,[25][26][27] and schoolchildren. 23,27 A birth cohort study found an association between total volatile organic compounds (TVOC) in the air at home at birth and development of atopic dermatitis at the age of 3 years.…”
Section: Introductionmentioning
confidence: 99%